Sustainable Management and Sustainable Development in Quran and Sunnah - Salem, Mamoon Yousef (Journal of Humanities & Social Sciences, 2019)
The study aims to clarify that words and sentences in the Holy Quran and Sunnah are rich in examples of sustainable management and development principles and their respective applications. In addition, the study confirms to non- believers living in this modern civilized world (Muslims or non- Muslims) that Islam supports and reinforces the implementation of sustainable management and development. It also highlights that Islam is suitable for all Mankind, wherever, whenever, and however, all through the span of life on this earth. The results of this study confirms that the Holy Quran and Sunnah are very rich in their terminology including words, sentences and phrases of sustainable management and development; Also Implementation of sustainable management and development is compulsory in Islam. In conclusion, the study offers some recommendations to increase and enhance awareness about Sustainable management and development such as the importance of legalization (Issuing legislations) to implement sustainable management and development based on Quran and Sunnah; Furthermore Islamic countries should support civilized human nature research which spreads Islam’s respect and Kindness towards other communities،